Abemaciclib and Vacuolin-1 decrease aggregate-prone TDP-43 accumulation by accelerating autophagic flux - Tanaka, Yoshinori; Kozuma, Lina; Hino, Hirotsugu; Takeya, Kosuke; Eto, Masumi (Biochemistry and biophysics reports, 2024)
(Macro)autophagy is a cellular degradation system for unnecessary materials, such as aggregate-prone TDP-43, a central molecule in neurodegenerative diseases including amyotrophic lateral sclerosis and frontotemporal lobar degeneration. Abemaciclib (Abe) and vacuolin-1 (Vac) treatments are known to induce vacuoles characterized by an autophagosome and a lysosome component, suggesting that they facilitate autophagosome-lysosome fusion. However, it remains unknown whether Abe and Vac suppress the accumulation of aggregate-prone TDP-43 by accelerating autophagic flux. In the present study, the Abe and Vac treatment dose-dependently reduced the GFP/RFP ratio in SH-SY5Y neuroblastoma cells stably expressing the autophagic flux marker GFP-LC3-RFP-LC3ΔG. Abe and Vac also increased the omegasome marker GFP-ATG13 signal and the autophagosome marker mCherry-LC3 localized to the lysosome marker LAMP1-GFP. The Abe and Vac treatment decreased the intracellular level of the lysosome marker LAMP1-GFP in SH-SY5Y cells stably expressing LAMP1-GFP, but did not increase the levels of LAMP1-GFP, the autophagosome marker LC3-II, or the multivesicular body marker TSG101 in the extracellular vesicle-enriched fraction. Moreover, Abe and Vac treatment autophagy-dependently inhibited GFP-tagged aggregate-prone TDP-43 accumulation. The results of a PI(3)P reporter assay using the fluorescent protein tagged-2 × FYVE and LAMP1-GFP indicated that Abe and Vac increased the intensity of the PI(3)P signal on lysosomes. A treatment with the VPS34 inhibitor wortmannin (WM) suppressed Abe-/Vac-facilitated autophagic flux and the degradation of GFP-tagged aggregate-prone TDP-43. Collectively, these results suggest that Abe and Vac degrade aggregate-prone TDP-43 by accelerating autophagosome formation and autophagosome-lysosome fusion through the formation of PI(3)P. •Abe and Vac accelerate autophagic flux.•Abe and Vac do not increase release of extracellular vesicles.•Abe and Vac autophagy-dependently suppress aggregate-prone TDP-43 accumulation.•Acceleration of autophagic flux by Abe and Vac is mediated by PI(3)P formation.